2019
DOI: 10.12659/ajcr.912727
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Renal Arteriovenous Malformation: A Rare but Treatable Cause of Hypertension

Abstract: Patient: Female, 29 Final Diagnosis: Renal arteriovenous malformation Symptoms: Hypertension Medication: — Clinical Procedure: Angiography Specialty: Cardiology Objective: Rare disease Background: Congenital renal vascular anomalies have been classified into 3 categories: cirsoid, angiomatous, and aneurysmal. These classifications are based on the size, location, and number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
10
0
2
Order By: Relevance
“…Several cases of renal AVMs have been reported that could not be diagnosed by CT examination or ultrasonography but were diagnosed by angiography, and most of them were caused by an abnormal vascular network corresponding to a type III AVM 3–6 . Color Doppler ultrasonography is inexpensive and the preferred initial diagnostic method for evaluation of the kidneys, and specific findings such as colored mosaic patterns can lead to the diagnosis of type I and II AVMs 7,8 . However, type III is difficult to diagnose with ultrasonography, likely because the complex, tiny, abnormal vascular networks are difficult to recognize.…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of renal AVMs have been reported that could not be diagnosed by CT examination or ultrasonography but were diagnosed by angiography, and most of them were caused by an abnormal vascular network corresponding to a type III AVM 3–6 . Color Doppler ultrasonography is inexpensive and the preferred initial diagnostic method for evaluation of the kidneys, and specific findings such as colored mosaic patterns can lead to the diagnosis of type I and II AVMs 7,8 . However, type III is difficult to diagnose with ultrasonography, likely because the complex, tiny, abnormal vascular networks are difficult to recognize.…”
Section: Discussionmentioning
confidence: 99%
“…El ultrasonido en modo bidimensional generalmente revela un área focal de lesiones quísticas con conexión irregular. El eco doppler color demuestra la presencia de flujo en estas áreas quísticas tortuosas, con un mosaico de colores que indica flujo turbulento (7,8) . En este caso no se detectaron cambios en la turbulencia del flujo mencionados en la literatura, probablemente porque la lesión era de bajo flujo.…”
Section: Discussionunclassified
“…Se puede pasar por alto una pequeña MAV renal debido a imágenes con secciones gruesas o un momento inapropiado; por lo tanto, se debe utilizar una TC de sección delgada con una colimación de al menos 1 mm y un intervalo de reconstrucción de 0,5 -1 mm (8) . Los hallazgos de la tomografía computada incluyen en la fase pre-contraste la presencia de hemorragia renal, calcificaciones del parénquima renal y de la pared vascular, masas redondas u ovales en el sistema colector; y en la fase post contraste se evidencia realce temprano de la vena renal ipsilateral y la VCI (8) . En los hallazgos tomográficos se identificó la adherencia de esta lesión a estructuras vecinas como músculo, vena cava inferior y tubo digestivo, sin plano graso de separación, manifestaciones del crecimiento extrarrenal de la lesión.…”
Section: Discussionunclassified
“…It has a prevalence of less than 0.04%. 1 , 2 The main clinical feature of AVM is sudden and uncontrollable hematuria, with or without a hack pair move. AVMs may be acquired, and the most common type is congenital renal AVM (CRAVM), which is present in approximately 20% of all renal AVM cases and in less than 1% of the general population.…”
Section: Introductionmentioning
confidence: 99%
“…3 , 4 CRAVM may cause hematuria leading to death. On the basis of vessel morphology, CRAVM has been classified into the following three categories: 2 the angiomatous type, which is characterized by a single large artery feeding multiple interconnecting distal branches and draining veins; the cirsoid type with multiple interconnecting varix-like malformed vascular bed-communications that lead to non-function of the focal glomeruli; 5 and the cavernosal type, which is caused by a pre-existing arterial aneurysm that invades and erodes an adjacent vein. 6 In CRAVM, the renal arteriovenous communication does not have a normal arteriovenous capillary network, but instead, it relies on an abnormal vessel (nidus) network.…”
Section: Introductionmentioning
confidence: 99%